Enhancing learning by retrieval: Enriching free recall with elaborative prompting. (June 2017) - Endres, Tino; Carpenter, Shana; Martin, Alf; Renkl, Alexander
Abstract: It is well-established in memory research that retrieval fosters learning. When applying this effect in education, it is an important question which type of retrieval task works best. Several studies have shown that learning is enhanced by linking new information with prior knowledge. A potential approach to making retrieval more effective, therefore, is to enrich retrieval instructions with the requirement to elaborate on the learning contents and link them to what is already known. In this study, we compared a free recall condition, as used in many studies on learning by retrieval, with a prompted recall condition in which learners were required to recall the information and apply it to their lives. Fifty-six undergraduate students were randomly assigned to one of these two conditions. They learned from a video-recorded lecture. One week later, learning outcomes were assessed by a posttest measuring fact recall and comprehension of the contents from the video lecture. Learners in the prompted recall group, compared to the free recall group, used more elaborative strategies in response to the recall task and achieved better comprehension scores. The effect on comprehension was mediated by the use of elaborative strategies. This pattern of results supports the constructive retrieval hypothesis, stating that retrieval is most effective when it involves constructive elaboration of the contents being learned. Our findings also encourage the use of pedagogical tasks in classroom teaching that combine elaboration and retrieval. Highlights: Enriching a free-recall task with an elaboration prompt fosters comprehension. This effect was mediated by more elaboration in the learners' recall protocols. Combining retrieval and elaboration can boost retrieval based learning.